Use of cryogenic machining to improve the adhesion of sphene bioceramic coatings on titanium substrates for dental and orthopaedic applications. Issue 5 (1st April 2019) - Biasetto, Lisa; Bertolini, Rachele; Elsayed, Hamada; Ghiotti, Andrea; Bruschi, Stefania
Abstract: Rods of commercially pure titanium were machined using standard oil-based emulsion and cryogenic cooling, and were then coated with sphene (CaTiSiO5 ) bioceramic by spray coating using an automatic airbrush. The sphene bioceramic was synthesized in-situ starting from a suspension of polysiloxane that used as SiO2 precursor, CaCO3 and TiO2 nanoparticles. The suspension was deposited on the machined substrates, which were heat treated up to 950 °C in order to promote the formation of sphene ceramic. The produced coated prototypes were characterized to evaluate the effect of the machining conditions on surface roughness and microstructure of the substrate, and thereby their effect on coating adhesion. Nanoindentation tests were employed to determine the hardness and elastic modulus of the coating through its thickness. Results showed that the reduced amount of defects on the surface of the cryo-machined substrates, contributed to increase the hardness, elastic modulus and adhesion strength of the coating-substrate interfaces compared to standard machined samples, therefore improving adhesion of the coating to the underlying substrate.